(untitled) (Plant Tissue Culture and Biotechnology, 2014)
In vitro response of four explants namely, leaf, shoot apex, nodal and internodal, in three stress tolerant Bangladeshi potato varieties, viz. Zaubilati, Shadaguti and Challisha were tested. Of all the varieties, Shadaguti responded best for all the explants. Among the explants nodal segment responded best, followed by shoot apex. For all these explants and varieties, shoot regeneration response was tested in response to two cytokines, BAP and Kn. When compared between BAP and Kn supplementation, Kn treatment performed better than that of BAP for nodal and shoot apex, while opposite was observed for remaining explants. Interestingly, hormone free basal PROP medium was found to be best for nodal explants of both Zaubilati and Challisha varieties. While nodal explants of Shadaguti showed the best result in 0.5 mg/l Kn. Shoot apex performed best in 0.5 mg/l Kn for all the varieties. As an explant both internode and leaf did not perform well. Direct regeneration from these explants was found best in PROP + 0.2 mg/l GA3 + 0.5 mg/l IAA; 1.0 mg/l BAP, 1.5 mg/l BAP and 2.0 mg/l BAP for Zaubilai, Challisha and Shadaguti, respectively. For rooting, of the in vitro grown shoots half strength of PROP medium supplemented with 0.5 mg/l IBA was found to be best. Cent percent survival of transplanted plantlets was recorded. The successful protocol for in vitro regeneration was developed which can be used for large scale production of these abiotic stress tolerant potato varieties. Plant Tissue Cult. & Biotech. 24(1): 101-109, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19218